«She’s not there» (around two Borges’ Poems) - Vázquez-Romero, José Manuel (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
Taking two of Borges’s poems, «Nostalgia del presente», and the couplet, «Le regret d’Héraclite», we attempt an analysis of the phenomenon of temporal and sensory experience of the moment. This initial analysis is approached from a Hegelian dialectic of the awakening from a state of the unconscious contrasted with the emptiness of identity and the heightened tensión when yearning is interposed. The diastasis or melancholy for the present before it has passed leads to the presence of absence (alterity and death).